THE GLOBAL DEVELOPMENT OF WOMEN’S SPORTS: TOWARDS GENDER EQUALITY - Ergasheva Muxlisa G‘ulomjon qizi, (Ustozlar uchun, 2025)
Introduction: In today’s era of globalization and increasing focus on social equity, gender equality in the field of sports has emerged as one of the most critical and actively debated topics. The global development of women’s sports represents not only a matter of athletic participation, but also a broader movement towards human rights, women’s empowerment, physical activity, and healthy lifestyles. Governments, international organizations, and civil society are steadily working to ensure that women’s participation in sports is protected, promoted, and expanded.  Until the early 20th century, women faced various social, cultural, and religious restrictions that limited their participation in sports. However, with the rise of the women’s movement, waves of feminism, and the global promotion of human rights, societal attitudes towards women in sports have undergone significant transformation. Today, women are increasingly active in nearly all areas of competition — from the Olympic Games to local sports leagues.  This article explores the historical phases of the development of women’s sports, the global struggle for gender equality in athletics, and the role and achievements of women in contemporary sports. Special attention is given to the policies and initiatives of international bodies such as the United Nations (UN), the International Olympic Committee (IOC), FIFA, and World Taekwondo (WT), all of which play a crucial role in shaping the future of women in sport.